Dawn and the impossible three - Martin, Ann M., 1955-; Galligan, Gale (Baby-sitters Club (Graphix (Firm)), 2017)
Dawn, the newest member of the Baby-sitters Club, gets more than she bargained for when her first job turns into a disaster and she has problems with Kristy.